2012
DOI: 10.1519/jsc.0b013e31822e58f8
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Strength on Different Resistance Training Rowing Exercises Predicts Start Phase Performance in Elite Kayakers

Abstract: This study aimed to examine the relationship existing between maximum strength values in 2 common resistance training row exercises (bilateral bench pull [BBP] and one-arm cable row [OACR]) and short sprint performance in elite kayakers. Ten junior kayakers (5 women and 5 men) were tested on different days for 1 repetition maximum (1RM) and maximal voluntary isometric contraction in both exercises. Moreover, a 12-m sprint kayak was performed in a dew pond to record split times (2, 5, and 10 m), peak velocity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 16 publications
4
43
0
3
Order By: Relevance
“…Together, these findings further support that heavy strength training can improve sprint abilities also in elite athletes that are specialized in an isolated upper-body poling movement. The pre-test correlations found here are in line with our previous study on ice sledge hockey (Skovereng, Ettema, Welde, & Sandbakk, 2013) and findings from other studies on explosive locomotion primarily using the upper-body for propulsion, such as maximal speed in double poling cross country skiing (Stoggl, Muller, Ainegren, & Holmberg, 2011) and the start phase in kayaking (Uali et al, 2012) and luge athletes (Crossland, Hartman, Kilgore, Hartman, & Kaus, 2011;Sheppard et al, 2012). However, the novelty of this study is the significant correlations of pre-to post-test changes in strength and sprint abilities that indicate that the strength gains were significantly associated with the improved sprint abilities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Together, these findings further support that heavy strength training can improve sprint abilities also in elite athletes that are specialized in an isolated upper-body poling movement. The pre-test correlations found here are in line with our previous study on ice sledge hockey (Skovereng, Ettema, Welde, & Sandbakk, 2013) and findings from other studies on explosive locomotion primarily using the upper-body for propulsion, such as maximal speed in double poling cross country skiing (Stoggl, Muller, Ainegren, & Holmberg, 2011) and the start phase in kayaking (Uali et al, 2012) and luge athletes (Crossland, Hartman, Kilgore, Hartman, & Kaus, 2011;Sheppard et al, 2012). However, the novelty of this study is the significant correlations of pre-to post-test changes in strength and sprint abilities that indicate that the strength gains were significantly associated with the improved sprint abilities.…”
Section: Discussionsupporting
confidence: 91%
“…Here, the correlation was strongest for the most movement-specific strength exercise when compared to more general strength measures. Associations between upper-body strength and various types of performances are further supported by studies on elite kayakers (Liow & Hopkins, 2003;Uali et al, 2012), wheelchair racers (Turbanski & Schmidtbleicher, 2010), surfers (Sheppard et al, 2012) and luge athletes (Crossland, Hartman, Kilgore, Hartman, & Kaus, 2011;Platzer, Raschner, & Patterson, 2009). A few of these studies also showed simultaneous improvements of maximal strength and sprint abilities with heavy upper-body strength training (Liow & Hopkins, 2003;Turbanski & Schmidtbleicher, 2010), whereas such training in cross-country skiers improved upper-body strength, skiing economy and endurance performance (Hoff, Gran, & Helgerud, 2002;Losnegard et al, 2011;Osteras, Helgerud, & Hoff, 2002;Ronnestad, Kojedal, Losnegard, Kvamme, & Raastad, 2012).…”
Section: Introductionmentioning
confidence: 81%
“…Jacobs (2009) showed that 12 weeks of upper body strength training, without any endurance training, increased peakVO 2 in paraplegic individuals. Similarly, the use of heavy strength training has been shown to increase upper body endurance capacity in kayaking (Ualí et al, 2012) and wheelchair racing (Turbanski and Schmidtbleicher, 2010). However, at present this theory is largely speculative in relation to the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Isometric strength tests are popular assessments that are widely used to assess maximum force-time curve characteristics of the muscular system for the lower [1][2][3] and upper limbs [4][5][6]. This strength testing method has been shown to be an effective approach for monitoring strength training adaptations, especially in well trained athletes who show only subtle changes even after long period of training [7,8], or to assess acute changes in performance during the recovery phase following high-volume resistance training sessions [9].…”
Section: Introductionmentioning
confidence: 99%